(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
This short speech is the author’s public greeting to Carlo Smuraglia on the occasion of the civil funeral in the Municipality of Milan. The memory of the commitment to the Resistance, of the profession of lawyer in defence of the weakest, of the leading role in Italian institutions and society, always on the side of legality and the Constitution